PRODUCT PERFORMANCE ANALYSIS OF “PRIMA” RICE SEED IN MALANG - Sony Prihandono; Any Suryantini (Tadulako University, 2015)
ABSTRACT The purpose of this study was to determine “Prima” seed product performance based on the perception of Malang farmers. This research was conducted in Malang during February to March 2015. The data usedin this study were primary data and secondary data. The number of respondents selected was 50 farmers who have used Ciherang “Prima” seed products. Importance and Performance Analysis (IPA) was applied in the analysis in this research. Product attributes of “Prima” seed is considered to have high performance and satisfy consumers are availability and productivity. Meanwhile, attributes that have lower performance and less satisfying consumers are price, cleanliness, volume and packaging. Key Words: Perception, performance, product analysis.